2001
DOI: 10.1038/sj.jhh.1001284
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and its reactivity in the offspring of first cousin hypertensive and first cousin normotensive parents: a preliminary report

Abstract: The aim of this preliminary study was to determine whether young offspring of first cousin hypertensive parent(s), have higher blood pressure (BP) reactivity in response to their first BP measurement, as compared to the offspring of first cousin normotensive parents. The BP of 135 boys aged 9-10 years was measured, for the first time ever, after a 10-min supine rest, and subsequently, twice at 10-min intervals. The offspring of first cousin hypertensive parent(s) reacted with signifi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In Oman, consanguinity is very common. Hassan et al [ 26 ] in their study, carried out in an urban sample of Omani population, found that 26% of the marriages were within their first cousin. At the national level this figure is very high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Oman, consanguinity is very common. Hassan et al [ 26 ] in their study, carried out in an urban sample of Omani population, found that 26% of the marriages were within their first cousin. At the national level this figure is very high.…”
Section: Discussionmentioning
confidence: 99%
“…At the national level this figure is very high. The first cousin marriage under the age of 50 years in 1995 was about 54% of total marriages [ 26 ]. This cultural practice may result into increase in both diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…3 Hassan et al has also reported the significant increase in diastolic pressure in offspring of hypertensive parents. 13 Even though p-value is not significant for heart rate between group-I and group-II, mean+SD is higher among individuals of group-I. Increased resting heart rate in offspring of single or both parent hypertensive has been associated with increase in cardiovascular morbidities.…”
Section: Discussionmentioning
confidence: 98%
“…Twin studies using mental stress tests reported significant h 2 for ΔSBP but not for Δ DBP (Busjahn et al, 1996;de Geus et al, 2007). Studies using stress to expose genetic variance focused mainly on the reactivity of BP in normal and /or probands of hypertensive subjects (Gottesman & Gould, 2003;Hassan et al, 2001;Rice et al, 1999). As BP itself is a complex phenotype controlled by several regulatory mechanisms, it was proposed that the study of intermediate traits, as compared to the final disease state, may have several advantages for the genetic dissection of complex diseases such as hypertension (Sing et al, …”
mentioning
confidence: 99%